2013
DOI: 10.1371/journal.pone.0067992
|View full text |Cite
|
Sign up to set email alerts
|

A Single Nucleotide Polymorphism within the Interferon Gamma Receptor 2 Gene Perfectly Coincides with Polledness in Holstein Cattle

Abstract: Polledness is a high impact trait in modern milk and beef production to meet the demands of animal welfare and work safety. Previous studies have mapped the polled-locus to the proximal region of the bovine chromosome 1 (BTA1) and narrowed it down to approximately 1 Mb. Sequencing of the positional candidate genes within the 1 Mb polled region and whole genome sequencing of Holsteins revealed a single nucleotide polymorphism (SNP) AC000158: g.1390292G>A within intron 3 of the interferon gamma receptor 2 gene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 18 publications
0
25
3
Order By: Relevance
“…This conclusion is inconsistent with that of Glatzer et al [5] who reported the existence of a progeny-proven heterozygous polled Holstein-Friesian sire that carried neither the P 80kbID mutation nor a Celtic mutation. Unfortunately, since the identity of this bull was not provided, we could not verify these results.…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…This conclusion is inconsistent with that of Glatzer et al [5] who reported the existence of a progeny-proven heterozygous polled Holstein-Friesian sire that carried neither the P 80kbID mutation nor a Celtic mutation. Unfortunately, since the identity of this bull was not provided, we could not verify these results.…”
Section: Resultscontrasting
confidence: 82%
“…In the past years, the position of the POLLED locus on BTA1 was refined [11,12] and candidate causal mutations were identified [2,4,5]. Recently, Medugorac et al [4] demonstrated the existence of at least two different alleles at the POLLED locus in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the significant expansion of the genomic sequence data in many aquaculture species, more and more studies have focus on the identification of SNPs in aquaculture species (Hayes, Laerdahl, Lien, Moen, Berg, Hindar, Davidson, Koop, Adzhubei & Høyheim 2007;Ciobanu, Bastiaansen, Magrin, Rocha, Jiang, Yu, Geiger, Deeb, Rocha, Gong, Kinghorn, Plastow, Van der Steen & Mileham 2010;Li, He, Yang, Shan, Tan & Gao 2010;Van Bers, Crooijmans, Groenen, Dibbits & Komen 2012). However, the association studies between the SNPs and the production traits for most aquaculture species, especially for the Chinese mitten crab, are still limited comparing with that in other domestic animals (Clop, Marcq, Takeda, Pirottin, Tordoir, Bib e, Bouix, Caiment, Elsen, Eychenne, Larzul, Laville, Meish, Milenkovic, Tobin, Charlier & Georges 2006;Daga et al 2013;Glatzer et al 2013;Kim et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…PCR direct sequencing with DNA derived from heterozygotes confirmed the SNP (Figure ). The risk allele was a candidate allele of polledness in Holstein (Glatzer et al, ). Polledness in cattle is an autosomal dominant trait; however, all heterozygotes had horns in this study.…”
Section: Resultsmentioning
confidence: 99%